2021
DOI: 10.1186/s12880-021-00560-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating treatment response to neoadjuvant chemoradiotherapy in rectal cancer using various MRI-based radiomics models

Abstract: Background To validate and compare various MRI-based radiomics models to evaluate treatment response to neoadjuvant chemoradiotherapy (nCRT) of rectal cancer. Methods A total of 80 patients with locally advanced rectal cancer (LARC) who underwent surgical resection after nCRT were enrolled retrospectively. Rectal MR images were scanned pre- and post-nCRT. The radiomics features were extracted from T2-weighted images, then reduced separately by leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Radiomics can extract large amounts of quantified features from medical imaging data to provide mineable highdimensional data. It deeply analyzes the clinicopathological information contained in large amounts of data [9,10] and has been applied to tumor staging [11][12][13], predicting treatment response [14][15][16][17], and assessing the efficacy after chemoradiotherapy [18][19][20] in rectal cancer patients. Although some studies have explored the application of radiomics in T staging of rectal cancer, most of these studies used radiomics features alone; few have incorporated the clinical factors with the radiomics features and lack preoperative experimental validation.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics can extract large amounts of quantified features from medical imaging data to provide mineable highdimensional data. It deeply analyzes the clinicopathological information contained in large amounts of data [9,10] and has been applied to tumor staging [11][12][13], predicting treatment response [14][15][16][17], and assessing the efficacy after chemoradiotherapy [18][19][20] in rectal cancer patients. Although some studies have explored the application of radiomics in T staging of rectal cancer, most of these studies used radiomics features alone; few have incorporated the clinical factors with the radiomics features and lack preoperative experimental validation.…”
Section: Introductionmentioning
confidence: 99%
“…All identified studies were performed on patients with LARC that were treated with nCRT followed by surgery with the aim of predicting tumour response using radiomics. 23 studies were excluded after full text review due to following reasons: 3 studies used contrast enhanced CT data that was not available in our dataset 21 , 45 , 46 , 4 studies used both pre and\or post treatment data 47 50 , 5 studies used pre-treatment multiparametric MRI (mpMRI) to develop a final signature with no standalone T2w MRI signature being reported 17 , 18 , 51 53 , 2 studies did not report any final signature 22 , 30 , 3 studies could not be reproduced as the radiomics workflow or feature definition was not clearly explained 25 , 54 , 55 , 1 study was excluded as the considered ROI was not the primarytumour 56 , 3 studies were excluded as authors reported failure of radiomics to predict the outcome of interest 57 59 , 2 studies were excluded as the reported signature was computed from feature maps, which are currently not supported by MIRP 28 , 60 . Finally, eleven studies were included for external validation analysis.…”
Section: Resultsmentioning
confidence: 99%
“…MR radiomics models with different ML classifiers (such as MLP, LR, SVM, DT, RF, and KNN, etc.) were developed for predicting tumor stages simplified as T(T1-T2) and N(N1-N2) stages [28], and tumor regression grades (TRGs) for evaluating the treatment response of LARC after neoadjuvant chemoradiotherapy (nCRT) of RC [29].…”
Section: Rectummentioning
confidence: 99%